Referential choice in stories with characters of one or different genders: A study of monolingual Croatian speakers. Issue 2 (April 2022) - Hržica, Gordana; Kuvač Kraljević, Jelena
During narration, speakers constantly choose appropriate referential forms (nominals or pronominals). Children may engage in this reference marking differently than adults. Discourse- or listener-oriented approaches make different predictions about referential behaviour in cognitively demanding situations: the first predicts a higher number of nominals; the second, a higher number of pronominals. The current study explores referential forms chosen by 50 children (6;0–6;11) and 50 adults, all monolingual speakers of Croatian, under the increased cognitive load of having to narrate a story from picture stimuli involving three characters of one or different genders. Generally, adults produce more referential expressions in their narratives. For both story types, children and adults use nominals more often than pronominals, children use a higher percentage of nominals than adults, and both groups use nouns to introduce and re-introduce characters. When maintaining characters in the narrative, both groups use more nouns and fewer pronouns in the story with characters of one gender, whereas they use fewer nouns and more pronouns in the story with characters of different genders. These findings suggest that Croatian monolingual adults and children more often use nominals for referencing in cognitively demanding stories, consistent with the discourse-oriented approach.